2022
DOI: 10.3389/fonc.2022.949688
|View full text |Cite
|
Sign up to set email alerts
|

Degradation strategy of cyclin D1 in cancer cells and the potential clinical application

Abstract: Cyclin D1 has been reported to be upregulated in several solid and hematologic tumors, promoting cancer progression. Thus, decreasing cyclin D1 by degradation could be a promising target strategy for cancer therapy. This mini review summarizes the roles of cyclin D1 in tumorigenesis and progression and its degradation strategies. Besides, we proposed an exploration of the degradation of cyclin D1 by FBX4, an F box protein belonging to the E3 ligase SKP-CUL-F-box (SCF) complex, which mediates substrate ubiquiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 85 publications
1
9
0
Order By: Relevance
“…Cyclin D1 (CCND1), or G1/S-specific cyclin-D1, is a protein encoded by the human CCND1 gene [ 30 , 31 ]. The genes for cyclin D1 belong to a highly conserved cell cycle family.…”
Section: Discussionmentioning
confidence: 99%
“…Cyclin D1 (CCND1), or G1/S-specific cyclin-D1, is a protein encoded by the human CCND1 gene [ 30 , 31 ]. The genes for cyclin D1 belong to a highly conserved cell cycle family.…”
Section: Discussionmentioning
confidence: 99%
“…44 The overexpression of cyclin D1 and c-myc has been detected in tumours, thus suggesting their oncogenic role and their targeting as a valuable anticancer strategy. 45,46 Ku70 and Ku80 are DNA-binding proteins involved in the mechanisms of DNA repair, and, in particular, in repairing double-strand breaks that are markers of cellular aging. 47 The Bax/Bcl2 heterodimers are onco-suppressors that activate the mitochondrial apoptotic pathway through their interaction with the mitochondrial voltage-dependent anion channel and the concomitant release of cytochrome c. 48 Both isoforms COX1 and COX2 of the cyclooxygenase enzyme are implicated in the biosynthesis of prostaglandins, e.g.…”
Section: Axial Aquo Ligandsmentioning
confidence: 99%
“…The overexpression of cyclin D1 and c-myc has been detected in tumours, thus suggesting their oncogenic role and their targeting as a valuable anticancer strategy. 45,46…”
Section: Experimental Observationsmentioning
confidence: 99%
“…Interestingly, several studies have shown that CCND1b has different functions from full-length CCND1a [30,31]. CCND1a can accelerate cell proliferation by promoting cell cycle progression, while CCND1b may inhibit cell cycle progression to prevent cell proliferation [31][32][33][34][35]. This unique activity of CCND1b is particularly significant in cancer treatment [36].…”
Section: Introductionmentioning
confidence: 99%